Marriage and Divorce Practices in the Society of Bandung: Contestation of Islamic and State Law - Diana Farid; Muhammad Husni Abdulah Pakarti; Iffah Fathiah; Hendriana Hendriana; Mohamad Hilal Nu'man (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2023)
Differences in marriage and divorce law in Islamic and state law One of the triggers for the initial causes of the disorderly implementation of marriage and divorce in the Sukajadi Bandung community was an understanding regarding the separation of religion and state law as well as social welfare factors related to law enforcement. This study analyzes the legal consequences, factors, and legal remedies that can be taken in unregistered marriages and divorces. The method used in this study is empirical-juridical with a qualitative approach. This approach is carried out to obtain information in the Sukajadi Bandung community regarding unregistered marriages and divorces. The results of the study show that the factors behind the rampant practice of unregistered marriages and divorces are not recorded because people's understandings of the dichotomy between Islamic law and that of the state are different. There is a link between the legal awareness of the community and its understanding of religion and welfare. In addition, unregistered marriages and divorces have an impact on the absence of marriage, inheritance, custody, and maintenance, which are detrimental to children and wives. Several efforts need to be made to minimize the occurrence of unrecorded marriages and divorces, including counseling, legal assistance for divorce victims, mediation, and consultation. This effort does not only involve the government and law enforcers but also preachers, lectors, and social organizations.